EXTENDED INTERVAL GENTAMICIN DOSING IN PRETERM INFANTS LESS THAN 35 WEEKS CORRECTED GESTATIONAL AGE. Issue 1 (14th December 2015) - McKitrick, Jarrid W R; Bewick, Brad; Ariano, Robert; Zelenitsky, Sheryl; Narvey, Michael; Jong, Geert W 't
Abstract : Objective: To confirm that gentamicin 5 mg/kg/dose every 48 hours in neonates less than 35 weeks corrected gestational age (CGA) results in the majority of gentamicin serum trough levels within the range of 0.5–2 mg/L and peak levels within the range of 6–12 mg/L. Design: Prospective pharmacokinetic (PK) analysis. Setting: Two neonatal intensive care units and one intermediate care unit in two tertiary care centres. Patients: Neonates less than 35 weeks CGA who received empiric gentamicin for sepsis between March 10 and June 10, 2014 in whom at least one gentamicin serum level was measured. Methods: PK analysis was performed following implementation of empiric dosing for gentamicin of 5 mg/kg every 48 hours in neonates. Results: Mean Cl, t1/2 and V1 were 42±10 mL/kg/h, 10.0±1.8 h, and 0.58±0.09 L/kg, respectively (n=54). A one-compartment pharmacokinetic model best represented the data. The mean Cl of gentamicin at 24 h post dose was significantly lower in neonates. Conclusions: Gentamicin 5 mg/kg q48h results in serum post dose levels between 6–12 mg/L 98% of the time compared to 5% of the time for once daily doses of 2.5 or 3 mg/kg. Gentamicin doses of 5 mg/kg q48h resulted in serum pre levels less than 0.5 mg/L 82% of the time (48 h post dose) compared to 9% of the time for once daily doses (24 h post dose). Increased clearance with advanced PNA suggests the need for more frequent dosing in neonates >14 days of age.